Research on the influence mechanism of creative time pressure on employee knowledge hiding: Evidence from creative service enterprises in China - Chen, Xiaoxia; Lin, Wenhe; Xu, Anxin (Frontiers in Psychology, 2022)
Employee knowledge sharing is critical to the success of creative service enterprises. However, knowledge hiding is prevalent in creative service enterprises. Using 381 advertising agency employees as respondents, we explored the mechanism of action of creative time pressure affecting knowledge hiding. We constructed a regulated dual-path model by drawing on affective event theory, with work passion as a mediating variable and team psychological safety climate as a moderating variable. The results show that creative time pressure increases employees’ knowledge hiding; creative time pressure mitigates knowledge hiding through the effect of harmonious passion, while obsessive passion enhances employees’ knowledge hiding; team psychological safety climate can regulate the relationship between creative time pressure and two types of work passion and the strength of the two paths. Therefore, the mediating effect of harmonious passion is stronger in a high team psychological safety climate, while the mediating effect of obsessive passion is stronger in a low team psychological safety climate.